The role of SET/I2PP2A in canine mammary tumors - Kake, Satoru; Tsuji, Shunya; Enjoji, Shuhei; Hanasaki, Sayaka; Hayase, Hiroshi; Yabe, Ryotaro; Tanaka, Yuiko; Nakagawa, Takayuki; Liu, Hao-Ping; Chang, Shih-Chieh; Usui, Tatsuya; Ohama, Takashi; et al. (Scientific reports, 2017)
Canine mammary tumor is the most common neoplasm in female dogs, and it has generated considerable attention as a translational model for human breast cancer. Ser/Thr protein phosphatase 2A (PP2A) plays a critical role as a tumor suppressor, and SET/I2PP2A, the endogenous inhibitory protein of PP2A, binds directly to PP2A and suppresses its phosphatase activity. Here, we investigated the role of SET in the tumorigenic growth in canine mammary tumor as well as in the sensitivity of tumors to existing therapeutics. Elevated protein levels of SET were observed in advanced-stage of canine mammary tumor tissues of dogs compared with paired normal tissues. Knockdown of SET expression in a canine mammary tumor cell line CIP-m led to increased PP2A activity and decreased cell proliferation, colony formation, and in vivo tumor growth. We observed suppression of mTOR, β-catenin, and NFκB signaling by SET knockdown. The sensitivity of CIP-m cells to doxorubicin was decreased by SET knockdown, while SET knockdown in CIP-m cells did not affect sensitivity to 4-OH-tamoxifen, carboplatin, bortezomib, and X-ray radiation. These data suggest that SET plays important roles in the tumor progression of a subset of canine mammary tumor by suppressing PP2A activity and enhancing mTOR, β-catenin, and NFκB signaling.